57.8k views
2 votes
(3-1) (4+2) + 9 - 3 I need help

User Crafty
by
6.5k points

2 Answers

2 votes

Answer:


\displaystyle 18

Explanation:


\displaystyle (3 - 1)(4 + 2) + 9 - 3 = [(2)(6)] + 9 - 3 = 12 + 9 - 3 = 12 + 6 = 18\:[OR\:21 - 3 = 18]

G - Grouping Symbols

E - Exponents

M\D - Division & Multiplication [left to right]

A - Subtraction & Addition [right to left OR vice versa]

I am joyous to assist you at any time.

User Iabbott
by
6.0k points
4 votes

Answer:

18

Explanation:

(3-1) (4+2) + 9-3 =

2 • 6 + 6 = 12 + 6

= 18

User Htmn
by
6.3k points